Micro-level development of Suliapadar watershed through construction of water conservation structures using geo-spatial technique - PAUL, J.C.; SAHU, A.P.; PARAMAGURU3, P.K.; NANDY, P.K.; MAHANTA, P. (Journal of Soil and Water Conservation, 2025)
Watershed management is widely acknowledged as an effective approach for mitigating soil erosion, facilitating water resource development, enhancing productivity, and promoting economic benefits. In this context, the present study employed Remote Sensing (RS) and Geographical Information System (GIS) techniques to conduct micro-level land and water resource planning in the Suliapadar microwatershed of the Korukonda block in Malkangiri district, Odisha, India. The main aim of this research was to develop GIS-based digital datasets at the watershed-scale that could be utilized by various agencies at the ground level for preparing watershed development plans and resource conservation strategies, thereby safeguarding the precious land and water resources of the study area. The study employed a two-step methodology comprising the preparation of diverse thematic maps such as the drainage map, slope map, land use/land cover map, and land capability map, followed by their superimposition to develop comprehensive land and water resource action plans for the study area. The resulting conservation map delineated various land conservation practices, such as afforestation, mango plantation, trenching, and water resource conservation structures like farm ponds, gully plugs, nala bunds, check dams, etc. This research will prove instrumental in safeguarding and enhancing both land and water resources and facilitate the pre-assessment of the impact of soil and water conservation measures before their implementation in the field